POLITIK HUKUM PIDANA Rekam Medis Sebagai Alat Bukti dalam Hukum Pembuktian Pidana - Marom, Ahmad Anfasul; Buamona, Hasrul (Al-Mazaahib: Jurnal Perbandingan Hukum, 2015)
Medical Currently, the relationship between doctor and patient is not just the relationship treatment alone, but he is also part of "therapeutic agreement" in which the patient is required to know and understand their rights and obligations in any effort to cure. One of the rights of patients in the treatment process is to get a record of treatment from a doctor or hospital, which in the world of health known as the Medical Record. But unfortunately, not many people who understand what it is and the importance of medical records for patients. Though medical record is valuable and important function for the patient, because it contains a description of a patient's medical history as well as actions taken by doctors in an effort to cure. In fact, not only that, the medical records could also be evidence in cases of alleged medical errors doctor sin handling/treating patients. This paper is going to study the problem of medical record as evidence in the criminal laws of evidence, especially in cases of alleged misconduct medical doctor.